Wait, what? : a comic book guide to relationships, bodies, and growing up - Corinna, Heather (Limerence Press, 2019)
Provides a humorous, illustrated guide to sex education, discussing topics such as puberty, gender, consent, sex, and sexual identity through a small group of young people asking the right questions. Includes activities and puzzles, sources for further resources, a glossary, and puzzle solutions.